Faricimab for treatment-resistant choroidal neovascularization (CNV) in neovascular age-related macular degeneration (nAMD): seven-months results using artificial intelligence and OCTA - Anna Heinke; Alexandra Warter; Ines D. Nagel; Akshay Agnihotri; Nehal Nailesh Mehta; Carlo Miguel B. Galang; Daniel N. Deussen; Dirk-Uwe G. Bartsch; Lingyun Cheng; Henry A. Ferreyra; William R. Freeman (International Journal of Retina and Vitreous)
Abstract Background To analyze the therapeutic response to faricimab 6 mg/0.05 ml in eyes with neovascular AMD (nAMD) with refractory intra- and/or subretinal fluid due to choroidal neovascularization (CNV), previously unresponsive to 4 mg monthly aflibercept and combination therapy with anti-VEGF and long-acting steroids. Methods A retrospective case series study of 22 eyes with unresponsive CNV, despite monthly intravitreal treatment (mean number of pre-faricimab injections: 35.52 ± 17.12). We evaluated therapeutic response in eyes with persistent intra/subretinal fluid (IRF/SRF) unresponsive to anti-VEGF double-dose (DD) monotherapy (4-mg aflibercept) and/or simultaneous DD anti-VEGF (4-mg aflibercept) with steroids (triamcinolone). Best-corrected visual acuity (BCVA), intraocular pressure (IOP), and optical coherence tomography (OCT) measurements of central retinal thickness (CRT) were recorded for 7 follow-ups. Baseline and follow-up OCTs were examined by an AI-developed platform (Discovery OCT Fluid and Biomarker Detector, RetinAI AG, Switzerland) to measure the volume of IRF, SRF, and pigment epithelium detachment (PED) in nanoliters (nL) and CRT in micrometers (μm). Paired t-test compared these parameters at baseline and after treatment. OCTA analysis of CNV before and after treatment with faricimab was conducted using Angio-Tool software. Results Anatomic outcomes included mean CRT reduction of -25.3 μm (p = 0.0118) at month-1, -16.15 μm (p = 0.0414) at month-4, and -26.36 μm (p = 0.0129) after the 7th follow-up. AI-assisted software analysis showed a significant reduction of IRF, SRF, and PED volume at multiple time points after initiating faricimab. There was a non-significant improvement in BCVA. Conclusions Switching to faricimab improved anatomy in highly treatment-resistant CNV eyes, indicating its potential when other therapeutic options have failed.